Activin A and Acvr2b mRNA from Umbilical Cord Blood Are Not Reliable Markers of Mild or Moderate Neonatal Hypoxic–Ischemic Encephalopathy - O'Sullivan, Marc Paul; Denihan, Niamh; Sikora, Klaudia; Finder, Mikael; Ahearne, Caroline; Clarke, Gerard; Hallberg, Boubou; Boylan, Geraldine B.; Murray, Deirdre M. (Neuropediatrics, 2021)
Background Activin A protein and its receptor ACVR2B have been considered viable biomarkers for the diagnosis of hypoxic–ischemic encephalopathy (HIE). This study aimed to assess umbilical cord blood (UCB) levels of Activin A and Acvr2b messenger RNA (mRNA) as early biomarkers of mild and moderate HIE and long-term neurodevelopmental outcome.Methods One-hundred and twenty-six infants were included in the analyses from the BiHiVE2 cohort, a multi-center study, recruited in Ireland and Sweden (2013 to 2015). UCB serum Activin A and whole blood Acvr2b mRNA were measured using enzyme-linked immunosorbent assay and quantitative polymerase chain reaction, respectively.Results Activin A analysis included 101 infants (controls, n = 50, perinatal asphyxia, n = 28, HIE, n = 23). No differences were detected across groups (p = 0.69). No differences were detected across HIE grades (p = 0.12). Acvr2b mRNA analysis included 67 infants (controls, n = 22, perinatal asphyxia, n = 23, and HIE, n = 22), and no differences were observed across groups (p = 0.75). No differences were detected across HIE grades (p = 0.58). No differences were detected in neurodevelopmental outcome in infants followed up to 18 to 36 months in serum Activin A or in whole blood Acvr2b mRNA (p = 0.55 and p = 0.90, respectively).Conclusion UCB Activin A and Acvr2b mRNA are not valid biomarkers of infants with mild or moderate HIE; they are unable to distinguish infants with HIE or infants with poor neurodevelopmental outcomes.
Keywords: biomarkers; Activin A; perinatal asphyxia; hypoxic–ischemic encephalopathy; neonatal encephalopathy; long-term outcome